2023
DOI: 10.30918/njas.111.23.003
|View full text |Cite
|
Sign up to set email alerts
|

Stem cuttings assessment for domesticating the medicinal melliferous plant, Combretum micranthum G. Don. in the Republic of Benin

Abstract: Combretum micranthum is a medicinal and melliferous plant from the dry tropical regions where it is threatened with extinction and it urges to develop suitable methods for its sustainable domestication. The challenges of producing seedlings from the seeds of the species make stem cutting, a potential approach for its domestication and this research evaluated the possibility to use such cuttings for seedlings production at a nursery located in the northern part of the Republic of Benin by determining the most e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Using forest surveys, Amakpe et al [ 23 ] and Yedomonhan et al [ 24 ] found that Combretaceae, and Fabaceae, were the most distributed silvo-melliferous plants families in the northern parts of Benin, and Kenali et al [ 20 ] found Fabaceae pollen dominance in the central parts of the country. Our investigations confirmed the dominance of these key families in the pollen content as the most frequent pollen species were Combretum micranthum, Aubrevillea herstingii, Cassia siamea and Detarium senegalensis .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Using forest surveys, Amakpe et al [ 23 ] and Yedomonhan et al [ 24 ] found that Combretaceae, and Fabaceae, were the most distributed silvo-melliferous plants families in the northern parts of Benin, and Kenali et al [ 20 ] found Fabaceae pollen dominance in the central parts of the country. Our investigations confirmed the dominance of these key families in the pollen content as the most frequent pollen species were Combretum micranthum, Aubrevillea herstingii, Cassia siamea and Detarium senegalensis .…”
Section: Discussionmentioning
confidence: 99%
“…Such contrasting situation supported that the most frequent plants were not the ones that dominated the honey pollen content in an ecological area. In fact, from the total of 42 trees species distributed in 18 families, that were identified as melliferous plants in 2012 [ 23 , 25 ] in the same area, pollens of only 26 trees and shrubs (61 %) were identified in honey samples in 2012, and 27 trees and shrubs (61 %) species were recorded in pollen 10 years later. The melliferous flora ecological distribution was dominated by Vitellaria paradoxa , Detarium microcarpum, Crossopteryx febrifuga and Terminalia sp which had the highest relative tree density and frequency [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations